2005
DOI: 10.4049/jimmunol.175.9.5675
|View full text |Cite
|
Sign up to set email alerts
|

Durable Human Memory T Cells Quantifiable by Cultured Enzyme-Linked Immunospot Assays Are Induced by Heterologous Prime Boost Immunization and Correlate with Protection against Malaria

Abstract: Immunological memory is a required component of protective antimalarial responses raised by T cell-inducing vaccines. The magnitude of ex vivo IFN-γ T cell responses is widely used to identify immunogenic vaccines although this response usually wanes and may disappear within weeks. However, protection in the field is likely to depend on durable central memory T cells that are not detected by this assay. To identify longer-lived memory T cells, PBMC from malaria-naive vaccinated volunteers who had received prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 37 publications
7
123
1
Order By: Relevance
“…Our previous studies had shown the ratio of cultured:ex vivo responses to be in the order of 15-30, even shortly after vaccination, but here the ratio for the blood-stage Ag was 3.4 at day 28 and only 1.3 at day 90. The cultured response also fell significantly from the day 28 to the day 90 level, where a plateau might have been expected, as in our previous studies [21,32]. The concept that effector and memory T cells are differently regulated is highlighted by the finding that the ex vivo and cultured responses did not correlate either at day 28 or day 90.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our previous studies had shown the ratio of cultured:ex vivo responses to be in the order of 15-30, even shortly after vaccination, but here the ratio for the blood-stage Ag was 3.4 at day 28 and only 1.3 at day 90. The cultured response also fell significantly from the day 28 to the day 90 level, where a plateau might have been expected, as in our previous studies [21,32]. The concept that effector and memory T cells are differently regulated is highlighted by the finding that the ex vivo and cultured responses did not correlate either at day 28 or day 90.…”
Section: Discussionsupporting
confidence: 78%
“…The main assays used in this study were ex vivo and cultured ELISPOT, which measure effector and memory T-cell responses respectively, as extensively characterized by us and others [19][20][21]. A range of parasite density was observed in the individuals studied, reflecting the biological variability of infection despite a standardized infection procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of naturally acquired immunity to CS protein demonstrated no correlation between cultured ELISPOT and ex vivo ELISPOT results [8]. The cells identified by cultured ELISPOT persist for at least 6 months after vaccination of naïve subjects, despite waning of cells detected by ex vivo ELISPOT [9]. The cells detected by cultured ELISPOT are here referred to as resting memory cells.…”
mentioning
confidence: 99%